Potential of lipase immobilized polyethersulfone (PES) membrane in biphasic reactor for oil hydrolysis - Hamidi, Faten Amira (2018)
Many green campaigns have initiated and spreading tons of awareness of the “greener Earth” by implementing more environmental-friendly methods and techniques in order to combat the current pollutions as well as employ the highest efficiency with an affordable cost. This study aimed to enhance the filtration process by incorporating enzyme to the membrane support system. In this study, an enzymatic membrane was applied to investigate the use of enzyme from bacteria origin that was able to enhance the separation of oil-water interfaces and as well as the effectiveness of the enzyme immobilization membrane. Lipase from Aspergillus niger origin is used to be immobilized onto the Polyethersulfone membrane. A membrane reactor with biphasic system was configured at laboratory scale in order to possess an organic-aqueous system with lipase immobilized membrane. The performance of the reactor was investigated with the olive oil hydrolysis in order to study the effect of the operating variables. The results found that the degree of hydrolysis (%) was the highest at 6- hour and with initial lipase concentration of 3 mg/ml which resulted in 0.11 mg/cm2 amount of lipase immobilized.